2018
DOI: 10.1177/0954008318802939
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermal atomic oxygen durable transparent silicon-reinforced polyimide

Abstract: A clear poly(amic acid) was reinforced by a trisilanolphenyl polyhedral oligomeric silsesquioxane (POSS) by direct dissolution, and transparent silicon-reinforced polyimide (Si-RPI) films with different POSS loadings were obtained after curing, showing high transmittance of >90% within 380–800 nm. The Si-RPI films were exposed to a ground hyperthermal atomic oxygen (AO) beam. The erosion depths and derived erosion yields of the materials decreased with POSS loadings. At a 20 wt% POSS loading, the Si-RPI sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…results confirmed that the designed double-layer brick-and-mortar structure with a denser top layer efficiently contributed to the AO-resistance of the double-layer PI-Mica film. This double-layer PI-Mica film also showed superior AO resistance (E = 0.17 × 10 −24 cm −3 atoms −1 ) over previously reported PI-based composite materials (Figure 3i and Table S2, Supporting Information) [4,8,11,13,31,[49][50][51] when the AO fluence reached 3.09 × 10 20 atoms cm −2 .…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…results confirmed that the designed double-layer brick-and-mortar structure with a denser top layer efficiently contributed to the AO-resistance of the double-layer PI-Mica film. This double-layer PI-Mica film also showed superior AO resistance (E = 0.17 × 10 −24 cm −3 atoms −1 ) over previously reported PI-based composite materials (Figure 3i and Table S2, Supporting Information) [4,8,11,13,31,[49][50][51] when the AO fluence reached 3.09 × 10 20 atoms cm −2 .…”
Section: Resultsmentioning
confidence: 50%
“…After AO exposure, the POSS transforms into a SiO 2 passivation layer on the surface, preventing AO from further eroding the PI films. [12][13][14] In addition, the mechanical properties of POSS-PI composite films are superior to those of pure PI films. [15] However, POSS monomer is expensive and its synthesis is complicated, making it difficult to produce for large-scale applications.…”
mentioning
confidence: 99%
“…6 Spacecraft that collide with ambient AO in LEO can have their components oxidized and eroded by the high translational energy of 4–4.5 eV and flux of 10 13 –10 15 atoms cm −2 s −1 . 7 Therefore, the development of an effective approach to enhance the AO resistance of CF/EP composites has received much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…A major thrust in current research has focused on the incorporation of AO-resistant moieties such as phosphine oxide or siloxane directly into the backbone of polymers to avoid the shape and CTE limitations of coatings. ,, In particular, the strategy of incorporating phenylphosphine oxide (PPO) groups into polymers has attracted widespread attention as a particularly effective way of imparting AO resistance. ,, Connell and co-workers at the NASA Langley Research Center pioneered a series of PPO-containing polymers and demonstrated their AO and oxygen plasma resistance. It was demonstrated that polymers containing 3–7 wt % phosphorus exhibited high glass transition temperatures ( T g ) and Young’s moduli . Based on these developments, a series of polyimides containing PPO have been prepared, but studies to understand the potential of PPO resistance to AO in other polymers have been limited. , …”
Section: Introductionmentioning
confidence: 99%
“…A major thrust in current research has focused on the incorporation of AO-resistant moieties such as phosphine oxide or siloxane directly into the backbone of polymers to avoid the shape and CTE limitations of coatings. 11,13,14 In particular, the strategy of incorporating phenylphosphine oxide (PPO) groups into polymers has attracted widespread attention as a particularly effective way of imparting AO resistance. 8,11,15 Connell and co-workers at the NASA Langley Research Center pioneered a series of PPO-containing polymers and demonstrated their AO and oxygen plasma resistance.…”
Section: ■ Introductionmentioning
confidence: 99%